Contribution of camera-trapping to the knowledge of Abrocoma boliviensis - Quiroga Pacheco, Carmen Julia; Hidalgo-Cossio, Marisol; Velez-Liendo, Ximena (THERYA, 2020)
Rare and endemic rodent species, such as the critically endangered Bolivian chinchilla rat, Abrocoma boliviensis, are infrequently captured using traditional trapping methods. Therefore, to determine their presence and abundance, indirect records (bird pellets, feces, bone remains) are often used. Although not a popular method for rodents, the incorporation of photography is known to provide precise data. Therefore, the objective of this report was to demonstrate the importance of using photographic records and occupancy models in the study of the distribution and ecology of a small-body species with high conservation value. We used photographic records obtained from 180 camera-trap nights in two areas of the Andean dry forests of Bolivia, during both wet and dry seasons. Data analysis include the estimates of presence probability of A. boliviensis in the study sites, using an exploratory occupancy analysis. The estimated presence probability of Abrocoma boliviensis for the study sites were 30.2 % during dry season and 33.9 % during wet season. However, due to the limited amount of photographic records for the species, it was not possible to accurately determine the factors affecting the species presence probability. Camera-trapping records and associated metadata provided new ecological and distribution data for the Bolivian chinchilla rat. In combination with information about threats that the species faces, our data may be useful in generating and applying conservation actions.